Using plant traits to explain plant–microbe relationships involved in nitrogen acquisition. Issue 3 (1st March 2015) - Cantarel, Amélie A. M.; Pommier, Thomas; Desclos-Theveniau, Marie; Diquélou, Sylvain; Dumont, Maxime; Grassein, Fabrice; Kastl, Eva-Maria; Grigulis, Karl; Laîné, Philippe; Lavorel, Sandra; Lemauviel-Lavenant, Servane; Personeni, Emmanuelle; et al.
Abstract : It has long been recognized that plant species and soil microorganisms are tightly linked, but understanding how different species vary in their effects on soil is currently limited. In this study, we identified those plant characteristics (identity, specific functional traits, or resource acquisition strategy) that were the best predictors of nitrification and denitrification processes. Ten plant populations representing eight species collected from three European grassland sites were chosen for their contrasting plant trait values and resource acquisition strategies. For each individual plant, leaf and root traits and the associated potential microbial activities (i.e., potential denitrification rate [DEA], maximal nitrification rate [NEA], and NH4 + affinity of the microbial community [NHScom ]) were measured at two fertilization levels under controlled growth conditions. Plant traits were powerful predictors of plant–microbe interactions, but relevant plant traits differed in relation to the microbial function studied. Whereas denitrification was linked to the relative growth rate of plants, nitrification was strongly correlated to root trait characteristics (specific root length, root nitrogen concentration, and plant affinity for NH4 + ) linked to plant N cycling. The leaf economics spectrum (LES) that commonly serves as an indicator of resource acquisition strategies was not correlated to microbial activity. These results suggest that the LES alone is not a good predictor of microbial activity, whereas root traits appeared critical in understanding plant–microbe interactions.